Kształtowanie krajobrazu rolniczego dla zachowania zrównoważonej gospodarki wodnej - Kędziora, Andrzej (Formation of agricultural landscape towards sustainable water management, 2007)
Water plays multiple roles in agricultural landscape. The most important are building a body of living organisms as well as materiał and energy transportation. Protection of suitable ąuantity and ąuality of water is indispensable condition for sustain functioning of rural areas. Unfortunately, so far errors madę in water management led to sever threats of water resources as well as their pollution. Water resources in Poland are one of the lowest in Europe. Improvement of their State is the crucial task for futurę development of national economy. The best tools for receiving this goal is formation of proper landscape structure leading to improvement of smali water retention as well as restoring the soil ability for water retention. Any activity leading to improvement of water condition of rural area must rely on two rules: to collect as much water and keep it as long as possible within the landscape looking for proper its allocation and use such agrotechnics which ensure maximal water flux flowing from the soil into atmosphere through the plant cover as evapotranspiration but not straight as simple evaporation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 404-416